Efektivitas Penggunaan Strategi Penjualan Melalui Go-Food Pada Umkm Kuliner Di Kenali Asam Atas Kota Jambi - Defi Haryani; M Nazori; G W I Awal Habibah (JOURNAL SAINS STUDENT RESEARCH, 2023)
The development of the culinary business cannot be separated from technological developments. However, digital transformation does not always go as well as expected because not all MSMEs are ready to run their business digitally. This study aims to dig deeper into the effectiveness of online sales strategies for culinary MSMEs that partner with the Go-Food application in Kenali Asam Atas Village. This study tries to look at the advantages and disadvantages of online sales, measured by the amount of profits earned compared to the losses experienced by merchants. The method used in this study was a qualitative approach, data collection techniques were carried out by interviews, observation, and documentation. The number of informants studied was 8 informants using purposive and snowball sampling techniques. The results of this study indicate that joining Go-Food has the following benefits: increasing the number of consumers, expanding the market, increasing income, time efficiency and increasing credibility. The advantages obtained by using an online promotion strategy through the Go-Food application are greater than the challenges faced so that researchers can conclude that the online promotion strategy through the Go-Food application is effective for the needs of culinary MSMEs. Using online marketing strategies, taking advantage of technological developments is a smart way to win market competition.